Incorporation of silver nanoparticles on Ti7.5Mo alloy surface containing TiO2 nanotubes arrays for promoting antibacterial coating – In vitro and in vivo study - Alves Claro, Ana Paula Rosifini [UNESP] (2018)
Bulk and surface properties are very important for materials used in biomedical applications. The development of new surface treatments, such as antibacterial coatings can directly affect the response of the surface. The purpose of this study was the development of antibacterial coating on the Ti7.5Mo alloy surface combining TiO2 nanotubes with silver nanoparticles incorporation using polydopamine assisted immobilization technique. Surface characterization analysis showed that silver nanoparticles were successfully immobilized. The concentration established was bactericidal, i.e., no bacteria grew after incubation. In vivo results showed that silver incorporation on the surface containing TiO2 nanotubes did not cause altered locomotor activity in zebrafish. On the other hand, it affected the cell adhesion on the surface. Thus, these results confirm the hypothesis that silver nanoparticles were totally incorporated to polydopamine on the surface containing TiO2 nanotubes and acted as the main mechanism the death of the bacteria by contact.